The Role of Sedation and Local Anesthesia in Acute Subdural Hematoma Surgery in the Elderly Popula-tion - Mustafa Cemil Kılınç; Alperen Kısa; Baran Can Alpergin; Emre Bahir Mete (Hitit Medical Journal)

(untitled)
Objective: In the elderly population, subdural hematoma represents a significant cause of morbidity and mortality. The surgical and anesthesia techniques for managing this condition have progressively evolved. Unlike numerous studies that compare chronic cases managed under general anesthesia and sedation, our study uniquely focuses on acute subdural hematoma cases. Material and Method: From 2020 to 2024, a retrospective study reviewed 54 patients aged 65 and older who underwent surgery for acute subdural hematoma. The patients were categorized into two groups: sedation (n=26) and general anesthesia (n=28). Data on surgical duration, hospital and intensive care unit stays, and mortality rates were collected from hospital archives. The general anesthesia group received midazolam, fentanyl, propofol, and rocuronium, while the sedation group received midazolam, fentanyl, and propofol. Subdural drains were universally placed and removed after postoperative brain computed tomography. Results: The mortality rate was significantly lower in the sedation group compared to the general anesthesia group (p=0.024). Surgical duration was shorter in the sedation group (p